2013
DOI: 10.4236/ajps.2013.46146
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Conversion of Carbohydrate Reserves from Pollen Maturation to Rehydration in a Chili Pepper

Abstract: Carbohydrate metabolism is critical for male fertility. Carbohydrate reserves (soluble sugars and starch) were quantified in three advanced stages of pollen development, from the final maturation to rehydration, in a chili pepper cultivar (Capsicum annuum L. cv. Calypso Red) with partially dehydrated pollen, to define possible carbohydrate inter-conversions. At the same time, the activity of soluble enzymes involved in sucrolysis and amylolysis were quantified to reveal potential metabolic pathways. The carboh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Rehydration of pollen is known to have consequences on the metabolic dynamics. A study with Capsicum annuum pollen showed that only 30 min incubation in an osmotic solution at room temperature led to significant pollen rehydration and changes in sugar content (García et al 2013 ). Furthermore, Ricinus communis seed, which, like pollen, is dry at maturity, showed marked metabolic changes upon rehydration at room temperature, with an accumulation of TCA metabolites (Ribeiro et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Rehydration of pollen is known to have consequences on the metabolic dynamics. A study with Capsicum annuum pollen showed that only 30 min incubation in an osmotic solution at room temperature led to significant pollen rehydration and changes in sugar content (García et al 2013 ). Furthermore, Ricinus communis seed, which, like pollen, is dry at maturity, showed marked metabolic changes upon rehydration at room temperature, with an accumulation of TCA metabolites (Ribeiro et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Drought and temperature stresses can severely affect starch accumulation, and absence of starch in mature pollen can be an indicator of pollen sterility [109,110,115,[190][191][192]. Endogenous starch is consumed during the first phases of pollen tube emission when pollen tube growth is at the expense of pollen reserves [193,194]. After this autotrophous phase, pollen grains obtain carbohydrates and other substances from the stigma and style.…”
Section: Adjustment Of Osmotic Pressure and Water Balance In Pollenmentioning
confidence: 99%
“…Koch, 2004 reviewed the role of acid invertase in plants; Three different acid invertases can be identified according to their location: vacuolar invertase (VIN), cytoplasmic invertase (CIN) and cell wall invertase (CWIN). The function of acid invertases in reproductive tissues has been intensely studied in different species such as lily [ 39 , 40 ], tobacco [ 41 , 42 ], tomato [ 33 ] and chilli pepper [ 43 ].…”
Section: Metabolite Profiles During Pollen Developmentmentioning
confidence: 99%